Perception of success and failure in EFL learning: investigating students’ attributional beliefs - Sobkowiak, Paweł (Studia Anglica Posnaniensia, 2025)
Research into attributional beliefs in English as a foreign language (EFL) learning has helped determine what factors contribute to learners’ academic success and failure, providing useful information for both teachers and students. Consequently, the former were prompted to find adequate instructional settings and make effective interventions in the classroom, whereas the latter – to take control of their own learning. By assigning causes of learning outcomes to external, changeable variables, within the individual’s control, such as students’ actions, scholars encouraged students to face their failures head-on, claiming they are essential to progress and fundamental to long-term success. Such an assumption was supposed to help develop a feeling of potency and agency in students, and build up self-esteem, ramping up their academic achievement. This article reports on an interview study carried out in the Polish educational context in the 2019/20 school year with a pool of 37 high school students, diversified by their language levels, age, gender, duration of learning and school grade, and aimed at investigating students’ perceived level of success and failure in learning English and its causal attributions. The research sought to examine how participants conceptualized the notion of success and self-assessed their linguistic aptitude and personal progress, and how those factors impacted self-perception as un/successful and in/competent. The analysis of students’ narratives, both positive and negative experiences with learning English allowed the author to identify a range of attributions.